Benchmarking computer systems for robot control - Machado, J. A. Tenreiro (1995)
The high computational burden posed by modern control algorithms often precludes their industrial application using present day microcomputers. We evaluate the computational load of different logical and arithmetic operations and the capabilities of several computing systems (software and hardware). Real-time limitations are alleviated through the adoption of general techniques associated with the data representation. Such techniques achieve not only a more efficient management of the computational resources but also provide a deeper insight on developments toward future computer control architectures